New Approach to Study the Ignition Processes of Organic Coal-Water Fuels in an Oxidizer Flow; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Valiullin T. R. Timur Radisovich (2016, 2016)
Title screen